Application of 3D printing individualized guide plates in percutaneous needle biopsy of acetabular tumors - Wu, Wen; Liu, Siyu; Wang, Lei; Wu, Bing; Zhao, Lulu; Jiang, Wenbo; Dai, Kerong; Hao, Yongqiang; Fu, Lingjie; Ai, Songtao (Frontiers in Genetics, 2022)
Objective: To investigate the effectiveness of applying the individualized guide plate which is based on digital image processing and 3D printing technology to percutaneous needle biopsy of periacetabular tumor. Methods: From July 2017 to August 2019, 11 patients (5 males and 6 females, aged 13 to 70 years old, mean 42.3 years old) with acetabular tumors diagnosed by needle biopsy in our hospital were enrolled in this retrospective study. Preoperative CT and MRI enhancement examination were performed routinely and the DICOM data was collected and imported into Medrawprint software. According to the specific anatomical morphology of acetabula, this study adopted the reverse calculation and direct design to print the individualized puncture guide plate using 3D printing technology. The puncture point and sampling approaches were determined by the guide plate morphology and the "double guide-hole and slide able groove" design. First, we evaluated the fitness of the 3D guide plate to the local anatomical structure, its assisted-puncture accuracy was estimated by imaging examinations, and postoperative complications were recorded. The accuracy of needle biopsy pathological result was estimated with reference to that of the tumor resection. Results: Our results showed that the 3D printing individualized guide plate matched the patients’ pelvic skin well, the puncture approach was consistent with the preoperative design, and no significant anatomical injuries including vascular and neural complications occurred after surgery. 9 patients’(90%) biopsy results were consistent with their postoperative pathological results, and 1 patient gave up the tumor resection. Conclusion: Based on digital image processing and 3D printing technology, the individualized guide plate can be used to guide the needle biopsy of acetabular tumors which makes the operation simpler and more precise.